PENGARUH IMPLEMENTASI KEBIJAKAN STANDARD OPERASIONAL PROSEDUR TERHADAP KINERJA PEGAWAI PT.PLN UNIT PELAYANAN PELANGGAN AMURANG - TORONGKANG, GLEDIS; LENGKONG, FLORENCE; LALOMA, ALDEN (Sam Ratulangi University, 2019)
Policy Implementation is one of the stages of public policy between the formation of policies and theconsequences of policies for the people they influence, the objectives of the policies. The purpose of this studyis to find out whether there is an influence on policy implementation on employee performance. Policyimplementation variables were measured and assessed using five dimensions and employee performancevariables were measured and assessed using twelve indicators. The method used in this study is aquantitative method that is measured using statistics. Data collection techniques used were observation anddistribution of questionnaires or questionnaires distributed to forty respondents. The results of the validityand reliability tests indicate that each statement item used is valid and reliable. Then from the results ofsimple linear regression analysis shows that every 1% addition to the value of the variable policyimplementation, then the value of the variable employee performance increases by 0.420, and it can be saidthat the direction of the variable influence on policy implementation to employee performance is positiveand significant. From the results of correlation analysis shows that the correlation value is 0.420, whichmeans the level of the relationship between policy implementation variables with the variable employeeperformance is included in the category of perfect correlation. Thus, it can be concluded that the proposedhypothesis can be tested empirically and with the underlying theories, and it is suggested to the partiesconcerned to continue to improve the quality of existing services and to continue to build public trust.Keyword: Policy Implementation, Employee Performance, Standart Operating Procedure